The Motif of the Angel(s) of Death in Islamic Foundational Sources - Prochwicz-Studnicka, Bożena (2020)
The article aims at presenting the motif of the angel(s) of death in the foundational texts of Islam, i.e. the Quran, and in the Sunnah of the Prophet Muhammad. The scope of the research was limited to the dynamic motifs and therefore involves only the angels who participate in events associated with the time in which a person dies. The first part of the present study provides an overview of the foundational sources of Islam and the second consists of an analysis of the eponymous theme which is featured in them. At the end, an attempt has been made to draw conclusions as far as the conceptual and imagery dimensions of the motif are concerned.
Keywords: Todesengel